Ketegasan Regulasi Laporan Ketaatan Syarian dalam Optimalisasi Financial Technology Lembaga Keuangan Syariah - Fahmi Firdaus; Agnes Febiola; Silvana Faiqoh (Perisai : Islamic Banking and Finance Journal, 2017)
Financial Technology in the digital era becomes an opportunity as well as a challenge for Islamic banks as one of Sharia Financial Institutions. Financial Technology for the customers. However, the current role of sharia banks has not been able to shift the position of conventional banks that are more inclusive, Islamic banks that can not guarantee the true quality of sharia. Regulations on the Sharia Compliance Report are not clearly identified as significant differentiators from conventional bank practices. The Weakness of Regulation of Bank Indonesia Regulation Number 10/16 / PBI / 2008 Article 2 on the Implementation of Sharia Principles has not guaranteed the performance of the true Islamic banks. The Shari'a Compliance Report is a mirror of the Shariah Enterprise Theory which states that the purpose of accounting is to provide information covering the efforts of stakeholders in performing devotion to Allah SWT to work on the triple bottom line (profit, human, and planet) model, given financial technology and distrust to use the services of sharia banks due to the negative image of Islamic banks.